Histochemical localization of secondary metabolites in Indigofera trita L.f. - J. ARANGANAYAKI; G. JAYANTHI (International Journal of Pharma and Bio Sciences, 2018)
Indigofera trita which belongs to the family Leguminosae has a huge number of medicinal properties. In order to explore and utilize this plant, the present study was undertaken to localize the secondary metabolites in leaf, stem and root. The results of present study showed identification and localization of secondary metabolites present in different region of this study plant. Micromorphological characters showed shield-like trichomes, amphistomatic stomata, spherical shaped cells with short and sharp horn-shaped ridges. The presence of the calcium oxalate crystals (druses) were observed in the leaf. This study would help in the identification of secondary metabolites like alkaloids, starch, proteins, tannins, phenols, reducing sugars, flavonoids, saponins and lipids in the plant tissues.